Platelet-Derived Growth Factor-Functionalized Scaffolds for the Recruitment of Synovial Mesenchymal Stem Cells for Osteochondral Repair - Yuan Luo; Xiaodong Cao; Junfeng Chen; Jianwei Gu; Hao Yu; Junying Sun; Jun Zou (Stem Cells International)
Cartilage regeneration is still a challenge for clinicians because of avascularity, denervation, load-bearing, synovial movement, and the paucity of endogenous repair cells. We constructed a multilayered osteochondral bionic scaffold and examined its repair capacity using a rabbit osteochondral defect model. The cartilage phase and interface layer of the scaffold were prepared by freeze-drying, whereas the bone phase of the scaffold was prepared by high-temperature sintering. The three-phase osteochondral bionic scaffold was formed by joining the hydroxyapatite (HAp) and silk fibroin (SF) scaffolds using the repeated freeze-thaw method. Different groups of scaffolds were implanted into the rabbit osteochondral defect model, and their repair capacities were assessed using imaging and histological analyses. The cartilage phase and the interface layer of the scaffold had a pore size of 110.13±29.38 and 96.53±33.72 μm, respectively. All generated scaffolds exhibited a honeycomb porous structure. The polydopamine- (PDA-) modified scaffold released platelet-derived growth factor (PDGF) for 4 weeks continuously, reaching a cumulative release of 71.74±5.38%. Synovial mesenchymal stem cells (SMSCs) adhered well to all scaffolds, but demonstrated the strongest proliferation ability in the HSPP (HAp-Silk-PDA-PDGF) group. Following scaffold-induced chondrogenic differentiation, SMSCs produced much chondrocyte extracellular matrix (ECM). In in vivo experiments, the HSPP group exhibited a significantly higher gross tissue morphology score and achieved cartilage regeneration at an earlier stage and a significantly better repair process compared with the other groups (P<0.05). Histological analysis revealed that the new cartilage tissue in the experimental group had a better shape and almost filled the defect area, whereas the scaffold was nearly completely degraded. The new cartilage was effectively fused with the surrounding normal cartilage, and a substantial amount of chondrocyte ECM was formed. The SF/HAp three-layer osteochondral bionic scaffold exhibited favorable pore size, porosity, and drug sustained-release properties. It demonstrated good biocompatibility in vitro and encouraging repair effect at osteochondral defect site in vivo, thereby expected to enabling the repair and regeneration of osteochondral damage.